Diffusion in and through solids - Rideal, E. K.
The general theory of diffusion is based upon analogy to the flow of heat through solid media, as is exemplified in the classical treatments of Fourier and also of Lord Kelvin in the Encyclopedia. In the actual process of diffusion of molecules and ions through and in soKds a whole set of new phenomena is observed. For example, hmitations on the magnitude of the diffusion potential are much more frequently imposed on these material systems by such factors as solubility or compound formation than are observed in systems m which the flow of heat alone is concerned. Again the flow of matter through solids is frequently composite in character, the various modes of transport being dependent on microheterogeneity, as is exemplified by lattice diffusion and movement along crystal boundaries, canals and capillaries, or even on molecular discontinuity as is the case when migration depends on the existence of molecular or ionic "holes" or vacant lattice points in a crystal. In studying the movement of material particles through a sohd, we must consider the nature of the interaction between diffusing material and diffusion medium. We may in a somewhat general manner note that either only dispersive or Van der Waals interactions are involved, or that electronic switches have taken place leading to chemi-sorption or chemical combination. Migration across a surface or through a solid medium may thus involve movement across an energy barrier from one position of minimum potential energy to another. At sufficiently high temperatures in the higher energy levels activated Surface migration naturally merges into free migration, with a consequent change in the temperature dependence of the diffusion.
Keywords: DIFFUSION